Plan Estratégico de Marketing para la Empresa Innovacompu de la Ciudad de Loja - Álvarez Jiménez, Armando Alexander (2016)
Currently the change is the essential characteristic in the business world, which is why the implementation of strategic marketing plans in companies has become very important because of the myriad of problems that these cross, the changing environment, competition, poor decision making, among others. For such circumstances this thesis general objective is to make a "Strategic Marketing Plan for Company Innovacompu Loja City", so that enables increased its share in the local market. The inductive method: To achieve these objectives in this research the following methods were used allowed define the need for a strategic marketing plan for the company to get to meet the objectives that arises. The deductive method was employed in the review of theories, concepts and general events about strategic marketing plan and its importance. As well as different techniques were also used to collect information, such as direct observation, interview with the manager of the company and surveys applied to 4 employees. The sample of surveys was applied to 381 families of the city of Loja; which allowed to detect the internal and external problems that the company faces. In the results the context was examined to know how the company can take measures against the variables "PESTEC", the five forces of Porter were studied to be able to determine the competitiveness of the company and its market share. The competitive profile matrix shows a good position of theentity with a value of 2.90 versus 2.60 and 2.50 that has the competition. It shows the strengths, opportunities, weaknesses and threats that, after being studied with the EFE and EFI matrices, are then analyzed in the high-impact SWOT matrix to determine the strategic objectives to be achieved. In the process of the discussion was first raised by the business philosophy to be known by all who work in the company to move towards its implementation and achieving your future goal, then the proposed strategic objectives is presented with their respective strategies, tactics, policies, goals, funding will contribute to the improvement and development of the organization, and will allow you to be more competitive and increase positioning and acceptance of the population of the city of Loja. Finally it is concerning the conclusions and recommendations are the result of our study, which will serve as a great contribution to the company to implement it presents.